Imam al-Nakhaʿī on Zakatable Wealth: Implications for Indonesia’s Regulatory Framework - Nur Rif'ah Syahirah Binti Haji Muhammad Kamal Shahrum; Ridhatullah Assya’bani (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study reinterprets Imam al-Nakhaʿī's methodological legacy—rooted in the early Kufan tradition of ra'y, qiyās, and the proto-Hanafi notion later formalized as istiḥsan—to develop criteria for defining zakatable wealth in contemporary economies. Using a doctrinal-comparative design, we (i) reconstruct al-Nakhaʿī's approach from classical reports and secondary scholarship; (ii) conduct a content analysis of Indonesia's Law 23/2011, Government Regulation 14/2014, MoRA Regulation 52/2014, and MUI Fatwa No. 3/2003; and (iii) contrast Indonesia's formulation with selected Malaysian practice (eg, payroll-based income zakat). The paper proposes a transferable decision matrix linking asset types (earned income/“al-māl al-mustafād,” business profits, securities, precious metals, digital/financial instruments) to normative parameters (ownership stability, growth potential, tradeability/liq uidity, and benefit realization) and to regulatory levers (niṣab benchmarks,ḥawlrequirements, net-vs-gross basis, withholding mechanisms, and hardship allowances/ḥadd al-kifaYes). Findings indicate that Indonesia's framework substantively accommodates dynamization of zakat objects but exhibits gaps of alignment—notably inconsistent treatment ofḥawland thisṣab for earned income, and ambiguity around net-of-needs calculations and financial assets. We argue that operationalizing an al-Nakhaʿī-inspired matrix can improve concept–rule coherence, guide harmonization across statute–regulation–fatwa, and furnish auditable standards for zakat agencies (eg, payroll deduction rules, asset-class worksheets, disclosure templates). Originality lies in explicitly translating an early Kufan method into concrete, testable regulatory criteria, thus bridging classical proposals with modern policy design.